Observations on “Anatomy of an R&R” and Other Reflections - Rynes, Sara L. (Academy of Management Journal, 2006)
The author recounts her experience serving as action editor for a three-person panel that was reviewing a paper submitted to the “Academy of Management Journal” for publication. As action editor it was her responsibility to apprise the paper's authors of the reviewers' critiques, which sometimes varied widely. As the manuscript was revised it sometimes became frustrating when reviewers held diverging opinions about the quality of the revisions. In the end, however, they did reach a consensus to publish the paper. Her advice to authors is to handle one's emotions constructively during the review process, and to try to see things from the editor's perspective.